Analysis of Current Limiter Electronics for Solar Pumps: Evaluating Performance in Varied Sunlight Intensities - Simanjuntak, Berkadh; Situmorang, Marhaposan; Sinambela, Marzuki; Bonardo, Doli (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This research investigates the implementation and efficacy of a current limiter electronics system within solar pump systems, focusing on its ability to regulate current under varying sunlight intensities, encompassing both strong and weak illumination conditions. To assess the system’s performance, an experimental setup integrates the solar pump system with the current limiter electronics, subjecting it to a range of sunlight intensities. Under optimal conditions, the current limiter adeptly controlled current flow, maintaining it within specified limits (2.54 A to 3.90 A) as incident sunlight intensity varied from 1000 W/mÂ³ to 2000 W/mÂ³. Equally impressive was the system’s capability to navigate reduced sunlight, adjusting current flow (1.20 A to 2.10 A) in response to lower intensities (500 W/mÂ³ to 1300 W/mÂ³). These findings not only advance our comprehension of current limiting techniques in solar pump systems but also offer valuable insights for future solar-powered system designs and implementations. Overall, the research underscores the vital role of a dependable current limiter electronics system in optimizing current flow across varying sunlight intensities, from strong to weak, within solar pump systems.